Solutions for Impulsive Fractional Differential Equations via Variational Methods. (14th April 2016) - Li, Peiluan; Wang, Hui; Li, Zheqing
Abstract : We investigate the boundary value problems of impulsive fractional order differential equations. First, we obtain the existence of at least one solution by the minimization result of Mawhin and Willem. Then by the variational methods and a very recent critical points theorem of Bonanno and Marano, the existence results of at least triple solutions are established. At last, two examples are offered to demonstrate the application of our main results.